1993
DOI: 10.1677/joe.0.136r001
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin Stimulates Testosterone Secretion by Rat Leydig Cells

Abstract: The present study was designed to evaluate the effects of endothelin (ET) on rat testicular steroidogenesis in vitro and the involvement of prostaglandins (PG) and extracellular calcium in its mechanism of action. To this purpose we examined the effects of ET-1 and ET-3 on basal testosterone secretion, the influence of ET-1 on PGE2 release, the interaction of ET-1 and ET-3 with human chorionic gonadotrophin (hCG) and the interference of indomethacin (an inhibitor of cyclooxygenase) and nifedipine (a calcium-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Our results are partially at variance with those of Filippini et al [15], who did not observe the presence of Ca 2+ influx in cultured TPMC. The underlying reasons in that study for a Ca 2+ response in TPMC to ET-1 so different from that of other vascular smooth muscle cells (VSMC), and from what we observed in TPMC, are difficult to assess; but one important factor might be that that study was performed on single attached cells, an experimental model characterized by a great degree of variability in cellular Ca 2 + response [32].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Our results are partially at variance with those of Filippini et al [15], who did not observe the presence of Ca 2+ influx in cultured TPMC. The underlying reasons in that study for a Ca 2+ response in TPMC to ET-1 so different from that of other vascular smooth muscle cells (VSMC), and from what we observed in TPMC, are difficult to assess; but one important factor might be that that study was performed on single attached cells, an experimental model characterized by a great degree of variability in cellular Ca 2 + response [32].…”
supporting
confidence: 53%
“…High-affinity receptors with the binding characteristics of ETA receptors are present in Leydig cells [12] and in the MA-10 murine Leydig tumor cell line [14]. In both cell types, ET-1 stimulates steroidogenesis, increasing basal and hCG-stimulated testosterone production in the former [15] and progesterone release in the latter [141. Autoradiographic studies have localized ET receptors in the testis also at the level of peritubular myoid cells [9,11], and it has recently been shown that these cells bind ET-1 with subsequent rapid intracellular Ca 2+ increase and production of inositol triphosphate [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, germ cell opioids [49] may be involved in the local control of Sertoli cell secretion of an argininevasopressin-like peptide that in turn regulates Leydig cell production of testosterone [50]. The demonstration that the germ cell 03-fibroblast growth factor is implicated in the regulation of rat Sertoli cell transferrin output [51] and the recent report of Onoda and Djakiew [43] showing that a 29-kDa protein isolated from round spermatids stimulates rat Sertoli cell transferrin synthesis raise questions about the exact nature of the germ cell paracrine factor(s) involved in the regulation of the synthesis of Sertoli cell transferrin as well as the paracrine factor involved in the control of Leydig cell testosterone synthesis [48,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…All experiments were performed soon after the death of the rat, which took place at 0900 h. Leydig cell purification was performed as previously described (Conte et al 1993). Immediately after death, the testes were removed and infused, via the testicular artery, with an enzyme solution (collagenase 0·5 mg/ml, soybean trypsin inhibitor 0·2 mg/ml, and leupeptin 5 µg/ml in HBSS containing 0·1% (wt/vol) BSA, pH 7·4) and then dispersed in enzyme solution in a shaking waterbath (20 min; 90 cycles/min; 34 C).…”
Section: Leydig Cell Purificationmentioning
confidence: 99%